Pengembangan Keterampilan Hidup dan Karir Siswa Sekolah Dasar dalam Rangka Peningkatan Mutu Lulusan Sekolah Dasar - I Komang Wisnu Budi Wijaya; Ni Wayan Sri Darmayanti; Ni Made Muliani (UHN IGB Sugriwa Denpasar, 2020)
This article aims to: 1) describe life skills and careers in the 21st Century and 2) analyze numerous possible strategies for advancing life skills and careers of elementary school students in the family, school, and community. The method used is a literature study. Various sources were collected and studied regarding the 21st Century competencies, characteristics of elementary school students, and the circumstances of educational institutions namely family, school, and community. The analysis technique used was the content analysis technique. It is the scientific analysis of the contents of various sources. The results stated that the 21st Century life skills and career consisted of several aspects, they were flexibility, adaptability, initiative and self-direction, social and cross-cultural skills, productivity and accountability, as well as leadership and responsibility. The advancement of life skills and career can be accomplished through centers of education by referring to each aspect of the skills and characteristics of each education center.